HUBUNGAN FAKTOR RISIKO DENGAN KEJADIAN OTITIS EKSTERNA DI POLIKLINIK THT-KL RSUD PROVINSI LAMPUNG TAHUN 2019 - Tondi Rosalinda Mandalahi; Mukhlis Imanto; Tri Umiana Soleha; Reni Zuraida (MAJORITY, 2023)
Otitis externa is an inflammation of the outer part of the ear which includes auricle, external audiotory canal, or both. The inflammation can be acute and chronic that ussually caused by bacteria, viral, and fungal infections. The objective of this study was to determine the association between risk factor with otitis externa occurrence in otorhinolaryngology head and neck surgery clinic of RSUD Abdul Moeloek Provinsi Lampung in 2019. This study was an observational analytic study with a case control design. The sample divided into 56 respondents who had otitis externa and 56 respondents who did not have otitis extena. The sample taken using consecutive sampling technique. Data analysis using chi square test (α = 0,05). Respondents who had otitis externa were highest among respondents with history of ear cleaning (62,5%), without history of activity in water (62,5%), and without history of diabetes mellitus (91,1%). The results of chi square analysis indicate an association between history of ear cleaning (p value = 0,001) and activity in water (p value = 0,036) with otitis externa occurrence. While history of diabetes mellitus (p value = 0,500) did not affect otitis externa occurrence. There was an association between history of ear cleaning and activity in water with otitis externa occurrence. While history diabetes mellitus did not affect the otitis externa occurrence.